Microscopic Concepts as a Need of the Macroscopic Knowledge in Thermology - Braga, Marcel B. P.; Kalhil, J. B. (Revista Cubana de Física; Vol 27 No 2 (2010), 2010)
Considering the difficulties in learning termology concepts in the Public High Schools of Manaus (Brazil), this study’s purpose is to show diagnostic experiences with the intent of minimize those learning difficulties and improve the teaching-learning process through the elaboration of physical models. Termology concepts are taught frequently in a way in which the relationship between cause and effect of the termal phenomena are not pointed out, presumably because they are based on different perspectives. Thus, it is necessary a conceptual and dialectical review of the different perspectives, given that they complement each other and are necessary for meaningful learning. We hypothesize that termology concepts are understood by the students in a superficial way, without scientific criteria of natural causes, and supported by their first experience of the senses, that is, by common sense. The methodological proposal is based on the use of physical models that incorporate alternative materials. In this way, we are looking to expose the fragility of using the senses as a way to understand termology concepts by showing their contribution in the process of assimilation; using the principles of logic and rationality; and providing favorable conditions for the manifestation of intuitive heuristics and creativity.